Perlindungan Hukum Hak Waris terhadap Anak Beda Agama dalam Perspektif Hukum Positif di Indonesia (Studi Kasus Putusan Mahkamah Agung Nomor: 1/Yur/Ag/2018) - Purba, Elisabet; Nalle, Viktor Imanuel Williamson (Wajah Hukum, 2025)
Legal protection in the implementation of the distribution of inheritance of different religions and legal developments in the implementation of the distribution of inheritance of different religions. These are two different legal views regarding the inheritance rights of children of different religions. The choice of rules used depends on the event being experienced. Even though the two are different, they complement each other. According to the inheritance law of the Civil Code, heirs from different religions are not an obstacle, whereas in Islamic inheritance law, different religions are an obstacle as heirs. This research aims to analyze and compare legal regulations regarding the division of inheritance between children of different religions and heirs from the perspective of the Compilation of Islamic Law (KHI) and the Civil Code (KUH Perdata). Apart from that, analyzing the progress of the solution is also very important in solving this problem. So that the judge who has the right to decide the case has determined that children of different religions can obtain their rights through a mandatory will. The development of this decision has also been in effect since the enactment of Supreme Court decision No.1/Yur/Ag/2018. Children of different religions can obtain rights through a mandatory will based on a judge's decision. This decision can provide certainty to people who experience problems regarding the inheritance rights of children of different religions.